Iron Oxide Mesoporous Magnetic Nanostructures with High Surface Area for Enhanced and Selective Drug Delivery to Metastatic Cancer Cells - Kheireddine El-Boubbou; Rizwan Ali; Sulaiman Al-Humaid; Alshaimaa Alhallaj; O. M. Lemine; Mohamed Boudjelal; Abdulmohsen AlKushi (MDPI AG, 2021)
This work reports the fabrication of iron oxide mesoporous magnetic nanostructures (IO-MMNs) via the nano-replication method using acid-prepared mesoporous spheres (APMS) as the rigid silica host and iron (III) nitrate as the iron precursor. The obtained nanosized mesostructures were fully characterized by SEM, TEM, DLS, FTIR, XRD, VSM, and nitrogen physisorption. IO-MMNs exhibited relatively high surface areas and large pore volumes (SBET = 70-120 m2/g and Vpore = 0.25-0.45 cm3/g), small sizes (~300 nm), good crystallinity and magnetization, and excellent biocompatibility. With their intrinsic porosities, high drug loading efficiencies (up to 70%) were achieved and the drug release rates were found to be pH-dependent. Cytotoxicity, confocal microscopy, and flow cytometry experiments against different types of cancerous cells indicated that Dox-loaded IO-MMNs reduced the viability of metastatic MCF-7 and KAIMRC-1 breast as well as HT-29 colon cancer cells, with the least uptake and toxicity towards normal primary cells (up to 4-fold enhancement). These results strongly suggest the potential use of IO-MMNs as promising agents for enhanced and effective drug delivery in cancer theranostics.